Chemistry of manganese deposits from the Hawaiian Archipelago - D J Frank; Maurice A Meylan; James D Craig; Geoffrey P Glasby (PANGAEA, 2023)
Selected manganese deposits from the Hawaiian Archipelago were submitted to chemical analysis using two methods. Atomic absorption spectrophotometry was used for the analysis of Fe, Mn, Al, Co, Cu, and Ni, while Ti was determined by X-ray fluorescence (XRF) using Energy Dispersive Analysis of X-rays (EDAX). After drying, each powdered sample was then treated with about 3 ml Aqua Regia (1 ml 16N HNO3 and 2 ml 6N HCl) and the solution was evaporated and prepared for analysis.